Impact of Arachidonic Acid and Docosahexaenoic Acid Supplementation on Tissue Fatty Acid Incorporation in the Young Pig (P09-009-19). (13th June 2019) - Hahn, Kaylee; Dahms, Irina; Butt, Christopher; Salem, Norman; Dilger, Ryan
Abstract: Objectives: Docosahexaenoic acid (DHA) and arachidonic acid (ARA) are conditionally essential fatty acids (FA) commonly supplemented in human infant formulas due to insufficient endogenous synthesis. Supplementation of these FA has been shown to yield FA profiles closer to those of a breastfed infant. The need for DHA supplementation in infant formula has been well-establish due to its positive influence on retinal and cognitive health. However, ARA supplementation recommendations have come under some scrutiny. This study aimed to use the neonatal piglet model to examine the impact of single and dual supplementation of ARA and DHA on tissue FA incorporation. Methods: Forty-eight male pigs were provided one of four dietary treatments ad libitum ( n  = 12 per treatment) from postnatal day 2 to 30. Dietary treatments included the following target ARA and DHA levels expressed as a percentage of total fatty acids: Diet 1 – Control (devoid of ARA and DHA), Diet 2 – 0.8% ARA, Diet 3 – 0.8% DHA, Diet 4 – 0.8% ARA + 0.8% DHA. Growth and food intake were measured daily. Plasma, red blood cells (RBC), and prefrontal cortex (PFC) were collected at study conclusion for FA analysis. Results: There were no significant differences ( P  > 0.05) between diet groups in food intake and overall growth. Pigs on diet 1 had lower ( P  < 0.001) ARA than those on diet 2 in the PFC, plasma, and RBC. Pigs on diet 3 had lower incorporation of ARA than those on diet 1 in the PFC ( P  < 0.001) and RBC ( P  = 0.03). Pigs on diet 4 had lower incorporation of ARA than those on diet 2 in the PFC ( P  < 0.001), plasma ( P  < 0.01), and RBC ( P  = 0.01). Pigs on diet 1 had lower ( P  < 0.001) DHA levels than those on diet 3 in the PFC, plasma, and RBC. There were no significant differences in DHA levels ( P  > 0.05) between diet 1 and diet 2 in PFC, plasma, or RBC. Pigs on diet 4 had lower incorporation ( P  < 0.01) of DHA than those on diet 3 in the PFC and plasma. Conclusions: These results show that PFC, RBC, and plasma ARA and DHA levels are sensitive to dietary intake when compared to diets devoid of these fatty acids. Results also indicate that endogenous ARA levels in the PFC and RBC are reduced when only DHA supplementation is provided in the absence of dietary ARA, hence the supplementation of ARA when DHA is provided may be warranted for maintenance of ARA concentrations in these tissues. Funding Sources: DSM Nutritional Products.